2013
DOI: 10.1007/s00039-013-0227-6
|View full text |Cite
|
Sign up to set email alerts
|

Modulus and Poincaré Inequalities on Non-Self-Similar Sierpiński Carpets

Abstract: Abstract. A carpet is a metric space homeomorphic to the Sierpiński carpet. We characterize, within a certain class of examples, non-self-similar carpets supporting curve families of nontrivial modulus and supporting Poincaré inequalities. Our results yield new examples of compact doubling metric measure spaces supporting Poincaré inequalities: these examples have no manifold points, yet embed isometrically as subsets of Euclidean space.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
53
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 32 publications
1
53
0
Order By: Relevance
“…We recall a construction studied in [, Section 1]. Let a=(a1,a2,) be a sequence of positive reals such that for any i the number 1ai is an odd integer strictly greater than one.…”
Section: Sierpinski Carpets Of Positive Two‐dimensional Lebesgue Measurementioning
confidence: 99%
See 3 more Smart Citations
“…We recall a construction studied in [, Section 1]. Let a=(a1,a2,) be a sequence of positive reals such that for any i the number 1ai is an odd integer strictly greater than one.…”
Section: Sierpinski Carpets Of Positive Two‐dimensional Lebesgue Measurementioning
confidence: 99%
“…Then any nonempty open subset of Sa is topologically one‐dimensional. If al2, then any nonempty open subset of Sa has positive two‐dimensional Lebesgue measure λ 2 , see [, Proposition 3.1 (iv)], and the restriction of λ 2 to Sa is Ahlfors 2‐regular. Examples In Figure on the right hand side we have an=12n+1l2, and so any nonempty open subset of the carpet Sa associated with this sequence a=(an)n1 has positive λ 2 measure.…”
Section: Sierpinski Carpets Of Positive Two‐dimensional Lebesgue Measurementioning
confidence: 99%
See 2 more Smart Citations
“…The construction in question undergoes by dividing each of the level n squares into a 2 n subsquares in an obvious manner and removing the middle square of the level n + 1 from each of the level n squares. In [MTW13] these carpets were studied in connection with Poincaré inequalities. Mackay et al showed that (S a , d, µ) supports a p-Poincaré inequality for p > 1 if and only if a ∈ ℓ 2 .…”
Section: Introductionmentioning
confidence: 99%